2015
DOI: 10.1007/s00232-014-9761-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of U18666a on Beta-Glucosidase, Sphingomyelinase, and Beta-Galactosidase Activities in Astrocytes of Young Rats

Abstract: Niemann-Pick type C disease (NPC) is a neurodegenerative genetic disorder caused by accumulation of lipids, especially cholesterol, in the perinuclear space. U18666A is a cholesterol transport-inhibiting agent, being used to mimic NPC, mainly in fibroblasts. The objective of this study was to observe the effect of the drug U18666A, which causes the accumulation of cholesterol in the cytoplasm of astrocytes from newborn rats, on some lysosomal hydrolase activities. Filipin staining and fluorescence microscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It has been shown that the antidepressant desipramine and related drugs induce the detachment of aSMase from the inner membrane leaflet of Lys with its consecutive inactivation, resulting in the accumulation of sphingomyelin [13]. The reduction of the aSMase activity has been also reported for other two CADs: the antiarrhythmic amiodarone and the inhibitor of cholesterol transport U18666A [21,22]. Furthermore, it has been reported that structurally different CADs have an additive effect on the inhibition of aSMase activity, arguing for action of these compounds on the same molecular target [13].…”
Section: Cationic Amphiphilic Drugsmentioning
confidence: 86%
See 1 more Smart Citation
“…It has been shown that the antidepressant desipramine and related drugs induce the detachment of aSMase from the inner membrane leaflet of Lys with its consecutive inactivation, resulting in the accumulation of sphingomyelin [13]. The reduction of the aSMase activity has been also reported for other two CADs: the antiarrhythmic amiodarone and the inhibitor of cholesterol transport U18666A [21,22]. Furthermore, it has been reported that structurally different CADs have an additive effect on the inhibition of aSMase activity, arguing for action of these compounds on the same molecular target [13].…”
Section: Cationic Amphiphilic Drugsmentioning
confidence: 86%
“…The interaction of CADs with membranes can modify their permeability as well as the membrane-proximal pH, thus affecting several biological processes in particular at the level of LE/Lys, such as the inhibition of several enzymatic activities and the change in the distribution of lysosomal enzymes [13,14,[18][19][20]. The acid sphingomyelinase (aSMase), a lysosomal enzyme which catalyzes the hydrolysis of sphingomyelin into ceramide and phosphorylcoline, is one of the targets of several CADs [13,21]. It has been shown that the antidepressant desipramine and related drugs induce the detachment of aSMase from the inner membrane leaflet of Lys with its consecutive inactivation, resulting in the accumulation of sphingomyelin [13].…”
Section: Cationic Amphiphilic Drugsmentioning
confidence: 99%
“…The treatment with U18666A resulted in an accumulation of cholesterol as expected, but moreover we observed gliosis in the control cells, demonstrated by a significantly increased number of GFAP + /vimentin + cells, accompanied by a reduced amount of phosphorylated GFAP and vimentin. Recent studies described U1866A induced cholesterol accumulations in rat astrocytes influencing the metabolic pathway of these cells [ 56 , 57 ], but effects in regards of gliosis were not topic of these studies.…”
Section: Discussionmentioning
confidence: 99%